Reinterprestasi Brain-Based Learning Berbantuan GeoGebra terhadap Keterampilan Berpikir Kreatif Siswa SMP - Sakinah Mawadah Warahmah; Adi Apriadi Adiansha; Nanang Diana; Muhammad Fuadi (MIKIR : Mathematics, Informatics, Knowledge And Information Research, 2026)
Creative thinking skills constitute a fundamental competency that students must master to meet the challenges of 21st-century mathematics learning. This study aimed to analyze the effectiveness of the Brain-Based Learning (BBL) model assisted by GeoGebra in improving the creative thinking skills of junior high school students in geometry. A quantitative approach with a quasi-experimental Non-Equivalent Control Group Design was employed, involving 64 seventh-grade students divided into an experimental class (n = 32) and a control class (n = 32). Data analysis included the Shapiro–Wilk normality test, Levene homogeneity test, paired and independent t-tests, N-Gain analysis, and Cohen's d effect size calculation. Results revealed that the experimental group's mean pretest score of 53.78 increased significantly to 70.16 in the posttest, while the control group improved from 51.03 to 61.31. The independent t-test yielded t = 4.2198 with p = 0.0001 (p < 0.05). The experimental group's N-Gain of 0.37 (moderate) exceeded the control group's 0.22 (low). Cohen's d = 1.055 confirmed a large effect of BBL assisted by GeoGebra.